Inspection And Diagnostics Of Railway Reinforced Concrete Bridge In Andijan-Khanabad Peregon (Eurasian Journal of Engineering and Technology, 2022)
The article presents practical recommendations for determining the load-carrying capacity of the railway reinforced concrete bridge located at 346+605 km of the Andijan railway distance Andijan-Khanabad. To ensure the safety of vehicles, it is recommended to build a new bridge or replace the main part of the bridge.